2014
DOI: 10.1007/s00125-014-3208-x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating betatrophin correlates with atherogenic lipid profiles but not with glucose and insulin levels in insulin-resistant individuals

Abstract: Betatrophin is a recently identified hormone, the circulating concentrations of which are unaltered in human insulin resistance but correlate significantly with atherogenic lipid profiles in high-risk cohorts with morbid obesity or type 2 diabetes. Betatrophin could therefore be a novel pathomechanistic player in dysfunctional lipid metabolism associated with high cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

30
185
18

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(233 citation statements)
references
References 11 publications
30
185
18
Order By: Relevance
“…Nevertheless, our findings did not accord with a recent study performed by Fenzl et al (15) in which serum betatrophin was found to be not elevated in patients with T2DM. The disparities may be due to the difference in sample sizes, oral hypoglycemic agents, and different disease duration of T2DM.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, our findings did not accord with a recent study performed by Fenzl et al (15) in which serum betatrophin was found to be not elevated in patients with T2DM. The disparities may be due to the difference in sample sizes, oral hypoglycemic agents, and different disease duration of T2DM.…”
Section: Discussioncontrasting
confidence: 99%
“…Even after adjustment for age and duration of Type 2 diabetes, the correlation between betatrophin and increments of C‐peptide concentration was still statistically significant, which suggests that insulin secretion deficiency is one of the factors that regulate betatrophin concentrations in humans. In contrast to previous results 7, 9, 10, we did not find a relationship between circulating betatrophin concentrations and BMI, HbA 1c or levels of blood lipids such as triglycerides and HDL cholesterol.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous reports have shown that age affects circulating betatrophin concentrations 7, 8, 9. In the present study, we found that betatrophin concentrations inversely correlated with the duration of Type 2 diabetes.…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, serum levels of this b cell effector are doubled in patients with type 1 diabetes mellitus (T1DM) as compared to age-matched healthy controls in a very recent study (6). Furthermore, Fenzl et al (7) demonstrated that the novel adipokine/hepatokine correlates significantly with an atherogenic lipid profile in small cohorts comprising of patients with morbid obesity or T2DM.…”
Section: Introductionmentioning
confidence: 98%
“…However, data on betatrophin regulation in humans so far is limited to patients with T1DM (6), morbid obesity (8), or T2DM (7,8,9), and there are no studies investigating betatrophin in GDM. Since betatrophin could potentially counteract impaired glucose control seen in GDM by improving b cell proliferation (5), our rationale was to investigate this novel adipokine/ hepatokine and its potential associations with other metabolic markers in human GDM.…”
Section: Introductionmentioning
confidence: 99%